Ecological Sanitation in Tropical Environments: Quantifying the Inactivation Rates of Microbiological Parameters During a Feces-Based Composting Process - Rose, Effebi Kokoh; Issouf, Ouattara; Nouho, Ouattara Koffi; Louis, Kouadio (European Scientific Journal, ESJ, 2017)
Dry composting toilets are increasingly being used as practical sanitation systems in areas with inadequate sewage disposal and inefficient (or inexistent) hydraulic network. In Côte d’Ivoire, the by-products from such systems are progressively used in peri-urban agriculture as organic fertilizer, most of the times regardless of any hygienic quality assessment; constituting thereby a major health risk. The main objective of this study was to assess the inactivation rates of key microbiological parameters [i.e., total coliforms (TC), fecal coliforms (FC), fecal streptococci (FS) and Ascaris lumbricoides (AL)] during the composting process of fecal matters from dry composting toilets. Feces from dry composting toilets pits located at Abobo- Sabgé, Abidjan, Côte d’Ivoire, were collected every two weeks from February to June 2017 and their microbiological contents, along with two physico-chemical characteristics (moisture content and pH) were analyzed. Results revealed noticeable concentration decreases for all the microbiological parameters, except AL. The concentrations dropped from 7.72 to 3.93, 7.61 to 2.70, and 7.10 to 3.11 (log FCU/g) for TC, FC and FS, respectively, during the monitoring period. Regarding AL, there was an increase during the first 29 days, then a decrease in their concentrations over the last 3 months. Furthermore, the study revealed that all fecal bacteria followed a first-order kinetic with the inactivation rates being 0.31, 0.24, and 0.21 d-1 for FC, TC and FS, respectively. The amount of fecal bacteria in the composts suggests that an additional time is required for maturation before any uses of such material as fertilizer.